Development of a fluorescent monoclonal antibody‐based assay to measure the allosteric effects of synthetic peptides on self‐oligomerization of AGR2 protein. (25th July 2013) - Gray, Terry A.; Murray, Euan; Nowicki, Matthew W.; Remnant, Lucy; Scherl, Alexander; Muller, Petr; Vojtesek, Borek; Hupp, Ted R.
Abstract Many regulatory proteins are homo‐oligomeric and designing assays that measure self‐assembly will provide novel approaches to study protein allostery and screen for novel small molecule modulators of protein interactions. We present an assay to begin to define the biochemical determinants that regulate dimerization of the cancer‐associated oncoprotein AGR2. A two site‐sandwich microtiter assay (2SMTA) was designed using a DyLight800‐labeled monoclonal antibody that binds to an epitope in AGR2 to screen for synthetic self‐peptides that might regulate dimer stability. Peptides derived from the intrinsically disordered N‐terminal region of AGR2 increase in trans oligomer stability as defined using the 2SMTA assay. A DSS‐crosslinking assay that traps the AGR2 dimer through K95‐K95 adducts confirmed that Δ45‐AGR2 was a more stable dimer using denaturing gel electrophoresis. A titration of wt‐AGR2, Δ45‐AGR2 (more stable dimer), and monomeric AGR2E60A revealed that Δ45‐AGR2 was more active in binding to Reptin than either wt‐AGR2 or the AGR2E60A mutant. Our data have defined a functional role for the AGR2 dimer in the binding to its most well characterized interacting protein, Reptin. The ability to regulate AGR2 oligomerization in trans opens the possibility for developing small molecules that regulate its' biochemical activity as potential cancer therapeutics. The data also highlight the utility of this oligomerization assay to screen chemical libraries for ligands that could regulate AGR2 dimer stability and its' oncogenic potential.